2011
DOI: 10.1007/s10096-011-1405-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of periodontal pathogens in newborns and children with mixed dentition

Abstract: We report the age-related prevalence of red complex periodontal pathogens, Porphyromonas gingivalis, Treponema denticola and Tannerella forsythia, along with 4 strains of orange complex pathogens. The bacteria present in samples isolated from tongue, cheek and subgingival sulcus in edentulous newborns and children with mixed dentition were monitored by PCR. P.gingivalis was not detected in any site of any subject in the two groups tested. However, T.denticola was not only found in the 6–13y group, but also in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
16
1
1
Order By: Relevance
“…P. gingivalis is considered to be a major pathogen in chronic periodontitis, but reports on its occurrence are inconsistent in children. Some authors did not find this bacterium independently of oral sample sites collected in periodontal healthy children with mixed dentition [Cortelli et al, 2012;Kimura et al, 2002] and others found P. gingivalis as well as P. intermedia and A. actinomycetemcomitans in supragingival plaque samples in 3-to 17-year-olds [Tanaka et al, 2006]. In the present study no significant differences were observed between the prevalence of the periodontopathogenic species A. actinomycetemcomitans and P. intermedia in BS and non-discoloured plaque samples.…”
Section: Discussioncontrasting
confidence: 44%
“…P. gingivalis is considered to be a major pathogen in chronic periodontitis, but reports on its occurrence are inconsistent in children. Some authors did not find this bacterium independently of oral sample sites collected in periodontal healthy children with mixed dentition [Cortelli et al, 2012;Kimura et al, 2002] and others found P. gingivalis as well as P. intermedia and A. actinomycetemcomitans in supragingival plaque samples in 3-to 17-year-olds [Tanaka et al, 2006]. In the present study no significant differences were observed between the prevalence of the periodontopathogenic species A. actinomycetemcomitans and P. intermedia in BS and non-discoloured plaque samples.…”
Section: Discussioncontrasting
confidence: 44%
“…P. gingivalis was seldom detected in the age groups younger than 19 years, and its presence was almost entirely related to the severity of periodontal disease (22). Later, the same authors examined 40 infants and 40 children, 6-13 years of age, for the abovementioned five species and, in addition, for Eikenella corrodens, Parvimonas micra and Treponema denticola (25). The authors hypothesized and confirmed that orange-complex bacteria (here including C. rectus, P. intermedia and P. micra, and, in addition, E. corrodens) accompany the initial colonization with bacteria of the red complex (P. gingivalis, T. forsythia and T. denticola), referring to the microbial associations among bacterial species in subgingival biofilms and color-coded complexes described by Socransky et al (150).…”
Section: Colonization Of Periodontal Pathogens In Children and Adolesmentioning
confidence: 99%
“…Although false-positive PATB findings have been reported, 8 no false-positive PATB reactivity due to Parvimonas has been described in the literature. P micra, formerly known as Peptostreptococcus micros, is a anaerobic gram-positive bacterium of the oral microflora 9,10 and an opportunistic pathogenic. This microorganism is mostly responsible for oral infections but can also cause pleural empyema, bone and joint infection, meningitis, and abscesses.…”
Section: Discussionmentioning
confidence: 99%